Kesalahan Penggunaan Preposisi Di Dan Ke Serta Prefiks Di- Dan Ke- Pada Karangan Narasi Pengalaman Study Tour Kelas Viii Smp - Amalia, Dian; , Prof. Dr. Abdul Ngalim, M.Hum (2017)
Writing skills is one of the skills that produced a result of writing that has meaning and is composed of a series of words that have a rule in writing. The sentence that ontains a write error in and to the front and the Word as a prefix is a way of writing the sentence does not match the pecified rule Enhanced Spelling (EYD). This research has two goals. (1) Describes the use of the Word error form the task ahead and the prefix on a study tour experience narrative essay grade VIII D and E SMP Negeri 7 Sukoharjo. (2) Describes the error analysis the use of prepositions and prefixes on the study tour experience narrative essay grade VIII SMP Negeri 7 Sukoharjo. This type of research uses descriptive itative research methods. Data from this research in the form of a narrative essay study tour experience. Engineering data collection performed by the method refer to proceed with engineering noted. Technique of data analysis is carried out using the method Agih. The results of this study found errors in the use and to the front and the Word as a prefix: 20 sentences containing words as errors in future, the 10 sentences which contain the prefix, as in 5 sentences containing words in future and to 1 sentence that contains the prefix to the in.